Immediate and Long-term Hearing Outcomes With the Middle Cranial Fossa Approach for Vestibular Schwannoma Resection. Issue 1 (January 2018) - Ahmed, Sameer; Arts, H. Alexander; El-Kashlan, Hussam; Basura, Gregory J.; Thompson, B. Gregory; Telian, Steven A.
Abstract : Objective: To analyze the immediate postoperative and long-term hearing outcome data in patients who have undergone hearing preservation attempts with the middle cranial fossa (MCF) approach for the resection of sporadic vestibular schwannoma. Study Design: Retrospective review of a surgical patient cohort. Setting: Tertiary academic referral center. Patients: Adult patients with unilateral sporadic vestibular schwannoma. Intervention: Surgical treatment with a MCF approach. Main Outcome Measure: Comparison of pre- and postoperative audiometric data in accordance with the 1995 and 2012 American Academy of Otolaryngology/Head and Neck Surgery guidelines on reporting hearing outcomes and with a word recognition score only scale. Long-term hearing outcome data were analyzed in the following postoperative groups: 3 to 5, 6 to 8, 9 to 11, and 12+ years after surgery. Results: From 1999 to 2016, 174 patients underwent the MCF approach and 155 of them met inclusion criteria for analysis of hearing outcome data. Class A or B hearing was preserved in 70% of the entire cohort after recovery. Seventy-one patients with measurable hearing met criteria for long-term data analysis. The rate of American Academy of Otolaryngology/Head and Neck Surgery class A or B hearing preservation was 82% at 3 to 5 years and declined thereafter. The rate of word recognition score class I or II hearing preservation was 98% at 3 to 5 years and declined less rapidly thereafter. Patients with preoperative Class A hearing had significantly higher rates of successful hearing preservation at all postoperative intervals. Conclusion: Delayed hearing loss occurs in a progressively increasing fashion but speech understanding remains durable for a majority of patients whose hearing is initially preserved with the MCF approach. Abstract : Supplemental Digital Content is available in the text